The Relationship Between Self Efficacy with Hypertension Degree - Yuliana Risa; Dwi Nur Aini; Maulidta Karunianingtyas Wirawati (Indonesian Journal of Global Health Research, 2022)
Hypertension is defined as blood pressure with the systolic above 140 mmHg and the diastolic pressure above 90 mmHg. Non-pharmacological therapies for the elderly are in the form of lifestyle modifications including diet patterns, physical activity, smoking bans, and self-efficacy. Self-efficacy helps a person in making choices, as well as persistence in maintaining the tasks that span their life. The purpose of this study was to determine the relationship between self-efficacy and hypertension degree at the Dempet Health Center, Demak Regency. This research is quantitative research with a cross sectional approach. This research was conducted on 36 samples using purposive sampling technique. Data processing used Spearman Rank correlation test. Most of the respondents had not confident self-efficacy of 15 respondents (41.7%). The results showed that as many as 15 respondents (42.8%) were categorized as Degree 3 hypertension. The results of the statistical test were p value = 0.000 and rcount = 0.914. Ha was accepted and H0 was rejected, it means that there was a relationship between self-efficacy and the degree of hypertension at the Dempet Health Center, Demak Regency.